Photo-Sintered Silver Thin Films by a High-Power UV-LED Module for Flexible Electronic Applications - Minha Kim (MDPI AG, 2021)
In recent printed electronics technology, a photo-sintering technique using intense pulsed light (IPL) source has attracted attention, instead of conventional a thermal sintering process with long time and high temperature. The key principle of the photo-sintering process is the selective heating of a thin film with large light absorption coefficients, while a transparent substrate does not heat by the IPL source. Most research on photo-sintering has used a xenon flash lamp as a light source. However, the xenon flash lamp requires instantaneous high power and is unsuitable for large area applications. In this work, we developed a new photo-sintering system using a high-power ultraviolet light emitting diode (UV-LED) module. A LED light source has many merits such as low power consumption and potential large-scale application. The silver nanoparticles ink was inkjet-printed on a polyethylene terephthalate (PET) and photo-sintered by the UV-LED module with the wavelength of 365 and 385 nm. The electrical resistivity as low as 5.44 × 10−6 Ω·cm (just about three times compared to value of bulk silver) was achieved at optimized photo-sintering conditions (wavelength of 365 nm and light intensity of 300 mW/cm2).